Tourism development in the north of Sweden - Lindström, Lisbeth; Örtqvist, Daniel (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2008)
The purpose of this study is to discuss and analyze an empirical investigation performed in the counties of Norrbotten and Västerbotten in Sweden. Specifically, the aim was to identify and value potentials and pitfalls in the development of tourism in the northern part of Sweden. In doing so we, among other things, discuss potential meeting places for interactivities, possibilities for collaboration, problem solutions and need for capacitating expressed from predecessor for officials, non profit organizations, educational sector and industrial life. The study results are based on a textual analysis of strategic documents and interviews with representatives for tourism business, organizations and officials. The content analysis of strategic documents from the municipalities represented in this research contains methods, aims and objectives for developing leisure and tourism. A total of 14 representatives from the county of Norrbotten and Västerbotten were interviewed and thereby contributed to the present study. It is possible to cluster these persons into four distinguished groups: 1) civil servants/destination developers from municipalities, 2) civil servants from county councils/university, 3) companies and 4) associations active with tourism activities. Civil servants from the municipalities Umeå, Skellefteå, Boden, and Piteå were interviewed. Two representatives came from the county of Västerbotten and one from the county of Norrbotten. One researcher from the county of Västerbotten was interviewed as well. Umeå and Skellefteå are situated in the county of Västerbotten and have 110 000 and 72 000 inhabitants respectively. Piteå and Boden with 41 000 and 28 100 inhabitants respectively are situated in the county of Norrbotten. Result from interviews of destination developers as well as entrepreneurs indicate clear possibilities for developing leisure and tourism in both counties. Furthermore, interview results underline that northern part of Sweden is interesting for several tourism groups as the brand has ...